Special auxiliary agent for improving conductivity of lithium iron manganese phosphate powder material and preparation and application thereof

By using conductive additives with specific structures in the synthesis of lithium manganese iron phosphate material, the conductivity and compaction density of the material are significantly improved, the problem of low material conductivity and lithium ion diffusion rate is solved, and the rate performance is improved and charge and discharge performance.

CN119431685APending Publication Date: 2025-02-14ANHUI XOANONS CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550036.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate materials have low performance in terms of conductivity and lithium ion diffusion, affecting their rate performance and charge and discharge performance.

Method used

Lithium manganese iron phosphate conductive additives prepared by ionization copolymerization of single-ended vinyl polyether monomers, vinyl monomers containing acid groups and other types of vinyl monomers by random radical aqueous solution.

Benefits of technology

The conductivity of lithium manganese iron phosphate powder material is significantly improved, and its compaction density is improved, the particle size and viscosity of the slurry are reduced, thereby reducing production energy consumption and improving product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431685A_ABST
    Figure CN119431685A_ABST
Patent Text Reader

Abstract

The invention discloses a special auxiliary agent for improving the conductivity of a lithium manganese iron phosphate powder material, and preparation and application thereof. The special auxiliary agent is prepared from a single-ended vinyl polyether monomer, a vinyl monomer containing an acidic group and other types of vinyl monomers under the action of an initiator and a chain transfer agent, and ionizing and copolymerizing by using a random free radical aqueous solution. The specific preparation method comprises the following steps: heating and refluxing a polymeric monomer, a chain transfer agent and a solvent in a reaction container, and reacting for a first period of time; adding an initiator and an ionization reagent solution under a reflux condition for reflux reaction for a second period of time; therefore, the lithium manganese iron phosphate conductive auxiliary agent is prepared. The lithium manganese iron phosphate conductive additive provided by the invention is used for preparing a lithium manganese iron phosphate material, and the conductivity of the lithium manganese iron phosphate can be remarkably improved. In addition, the carbon content and the compaction density of the lithium manganese iron phosphate product are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of synthesis of special auxiliary agents for preparing lithium manganese iron phosphate powder materials. Background Art

[0002] Lithium manganese iron phosphate (LiMn x Fe 1-x PO4, LMFP for short) is a new type of positive electrode material for lithium-ion batteries, which has attracted widespread attention due to its high energy density and good safety. It is synthesized by manganese doping on the basis of lithium iron phosphate (Li FePO4, LFP for short), and its appearance improves the energy density of the material. Like LFP, LMFP has an olivine structure, in which PO4 tetrahedron provides structural stability. However, LMFP also faces the challenges of low electronic conductivity and lithium ion diffusion rate, which affect its rate performance and charge and discharge performance under high current.

[0003] During the entire manufacturing process of positive electrode materials such as lithium manganese iron phosphate, attention should be paid to the improvement of the physical and chemical parameters of LMFP. Therefore, how to improve the conductivity of this type of powder material during the synthesis of positive electrode materials such as lithium manganese iron phosphate is an urgent problem to be solved. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a special additive for improving the conductivity of lithium iron manganese phosphate powder material (referred to as: lithium iron manganese phosphate conductivity additive) and its preparation and application. The lithium iron manganese phosphate conductivity additive is applied to the synthesis process of lithium iron manganese phosphate, which can significantly improve the conductivity of the powder material and increase the compaction density of the powder material.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a special additive for the conductivity of lithium manganese iron phosphate powder material, which is prepared by random free radical aqueous solution ionization copolymerization of a single-end vinyl polyether monomer, a vinyl monomer containing an acidic group and other types of vinyl monomers under the action of an initiator and a chain transfer agent.

[0007] Furthermore, the structural formula of the lithium manganese iron phosphate conductive additive is as follows:

[0008]

[0009] Where: R1 is -H or -CH3

[0010] R2 is -O-(CH2-CH-O) n -H or -COO-(CH2-CH-O) n -CH3;

[0011] R3 is -H or -CH3;

[0012] R4 is an alkyl group, a phenyl group, a pyridyl group, a pyrrolidone group, a phenol group or a benzoic acid group;

[0013] M represents potassium ion, sodium ion, tetramethylammonium cation or hydrogen cation;

[0014] a, b, c are positive integers.

[0015] Furthermore, the single-end vinyl polyether monomer is selected from one or a combination of two or more of allyl polyoxyethylene ether (HPEG), single-end methyl polyoxyethylene acrylate (MPEGA), and single-end methyl polyoxyethylene methacrylate (MPEGMA).

[0016] The vinyl monomer containing an acidic group is selected from any one of acrylic acid, methacrylic acid, itaconic acid and 4-vinylbenzoic acid or a combination of two or more thereof.

[0017] Other types of vinyl monomers are selected from any one or a combination of two or more of styrene, benzyl methacrylate, benzyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylate, dodecyl methacrylate, dodecyl acrylate, hexadecyl methacrylate, hexadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, isobornyl methacrylate, isobornyl acrylate, vinyl pyridine, N-vinyl pyrrolidone, and 4-vinyl phenol.

[0018] Furthermore, the mass ratio of the single-end vinyl polyether monomer, the vinyl monomer containing an acidic group, and other types of vinyl monomers is 1-90:1-60:1-60.

[0019] On the other hand, the present invention provides a method for preparing a lithium manganese iron phosphate conductive additive, comprising the following steps: adding a single-end vinyl polyether monomer, a vinyl monomer containing an acidic group, and other types of vinyl monomers, a chain transfer agent, and a solvent to a reaction container, heating and refluxing, and reacting for a first period of time; adding an initiator and an ionizing agent solution under reflux conditions, and refluxing for a second period of time. Thus, the lithium manganese iron phosphate conductive additive of the present invention is prepared.

[0020] Furthermore, in the preparation method of lithium manganese iron phosphate conductive additive, the solvent used is deionized water.

[0021] Furthermore, the initiator used is a water-soluble azo initiator or a water-soluble peroxide compound initiator; the water-soluble azo initiator is selected from any one of water-soluble azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, and azobisisopropylimidazoline; the peroxide compound initiator is selected from any one of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0022] Furthermore, the ionizing agent used is selected from any one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, tetramethylammonium hydroxide and ammonium bicarbonate.

[0023] Furthermore, the chain transfer agent used is selected from any one of mercaptoethanol, thioglycolic acid, n-butyl mercaptan, tert-butyl mercaptan, n-octyl mercaptan, and n-dodecyl mercaptan.

[0024] On the other hand, the present invention provides an application of a special additive for improving the conductivity of lithium iron manganese phosphate powder material in the preparation of lithium iron manganese phosphate powder material.

[0025] The beneficial effects of the present invention are as follows: the lithium iron manganese phosphate conductive additive provided by the present invention is used for the preparation of lithium iron manganese phosphate powder material, and it can significantly improve the conductivity of the powder material. In addition, the carbon content and compaction density of the lithium iron manganese phosphate powder material are also improved. When the lithium iron manganese phosphate conductive additive is used for the preparation of lithium iron manganese phosphate slurry, the particle size and viscosity of the prepared lithium iron manganese phosphate slurry can also be reduced, thereby reducing the energy consumption of producing lithium iron manganese phosphate powder material and improving product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the infrared spectrum of the product in Example 1.

[0027] Figure 2 This is the infrared spectrum of the product in Example 5.

[0028] Figure 3 This is the infrared spectrum of the product in Example 11.

[0029] Figure 4 This is the infrared spectrum of the product of Example 12. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the examples. Unless otherwise specified, the raw materials and reagents used in the present invention are purchased from the market.

[0031] The present invention provides a lithium manganese iron phosphate conductive additive, which may be specifically implemented by the following steps: adding a single-end vinyl polyether monomer, a vinyl monomer containing an acidic group and other types of vinyl monomers, a chain transfer agent, and a solvent to a reaction container, heating and refluxing for a first period of time; adding an initiator and an ionizing agent solution under reflux conditions, and refluxing for a second period of time. Thus, the lithium manganese iron phosphate conductive additive of the present invention is prepared.

[0032] When adding the initiator and ionizing agent solution for the second period of reflux reaction, the reflux reaction can be performed step by step. For example, an aqueous solution containing the initiator and the ionizing agent can be prepared in advance, and part of the prepared solution can be added first, and the remaining solution can be added after a period of reaction, or the remaining solution can be added in multiple times for reaction.

[0033] Specifically, all monomers and part of deionized water can be added to the reaction bottle, the temperature is raised and refluxed for a period of time, and the aqueous solution of the initiator and the ionizing agent is added dropwise, the dropping process is 1-3 hours, and the reflux reaction is carried out for 0.5-3 hours after the dropping is completed. The aqueous solution containing the initiator and the ionizing agent is prepared in advance. When the previous reflux reaction is completed, the aqueous solution containing the initiator and the ionizing agent is added dropwise, and the reflux reaction is carried out for 1-2 hours after the dropping is completed, and the aqueous solution containing the initiator and the ionizing agent is continued to be added dropwise, and the reflux reaction is carried out for 2-5 hours after the dropping is completed, and finally a solution containing the product of the present invention is obtained.

[0034] The single-end vinyl polyether monomer is selected from one or a combination of two or more of allyl polyoxyethylene ether (HPEG), single-end methyl polyoxyethylene acrylate (MPEGA), and single-end methyl polyoxyethylene methacrylate (MPEGMA).

[0035] The vinyl monomer containing an acidic group is selected from any one of acrylic acid, methacrylic acid, itaconic acid and 4-vinylbenzoic acid or a combination of two or more thereof.

[0036] Other types of vinyl monomers are selected from any one or a combination of two or more of styrene, benzyl methacrylate, benzyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylate, dodecyl methacrylate, dodecyl acrylate, hexadecyl methacrylate, hexadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, isobornyl methacrylate, isobornyl acrylate, vinyl pyridine, N-vinyl pyrrolidone, and 4-vinyl phenol.

[0037] The initiator used is a water-soluble azo initiator or a water-soluble peroxide compound initiator; the water-soluble azo initiator is selected from any one of water-soluble azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, and azobisisopropylimidazoline; the peroxide compound initiator is selected from any one of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0038] The ionizing agent used is selected from any one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, tetramethylammonium hydroxide and ammonium bicarbonate.

[0039] The chain transfer agent used is selected from any one of mercaptoethanol, thioglycolic acid, n-butyl mercaptan, tert-butyl mercaptan, n-octyl mercaptan and n-dodecyl mercaptan.

[0040] The specific embodiments are as follows.

[0041] Example 1

[0042] In a reaction four-mouth bottle equipped with a stirrer, a reaction condenser, a thermometer and a dropping funnel, add 90 grams of allyl polyoxyethylene ether (HPEG) monomer, 60 grams of acrylic acid, 60 grams of isobornyl methacrylate, 1.3 grams of thioglycolic acid (chain transfer agent), and 70 grams of deionized water, and reflux for half an hour. Under reflux conditions, a solution consisting of 60 grams of 0.17M potassium hydroxide water (ionizing agent) solution and 2.6 grams of hydrogen peroxide (peroxide compound initiator) is added dropwise. After the addition is complete, the reaction is continued for 1 hour, and then the solution consisting of 0.4 grams of hydrogen peroxide and 14 grams of 0.17M potassium hydroxide (ionizing agent) is added twice, each time at an interval of 1 hour. After the last addition, the reaction is continued at this temperature for 5 hours until the polymerization is complete. Test the infrared spectrum, acid value and solid content.

[0043] Figure 1 This is the infrared spectrum of the product of Example 1. It can be seen from the figure that at the wave number of 2884.93cm -1 There is a very broad absorption peak near 2963 ± 10 cm -1 and 2972±10cm -1 Typical stretching vibration absorption peak of methyl group, 2926±10cm -1 and 2856±10cm -1 The broad absorption peak is composed of the typical stretching vibration absorption peak of methine. 3477.17cm -1 There is a broad absorption peak, which is a typical absorption peak of carboxyl hydroxyl stretching vibration. 1730.97cm -1 This is a typical carbonyl stretching vibration absorption peak in an ester group. 1461.81cm -1 It is the absorption peak of methine deformation vibration, 1108.48cm-1 It is the stretching vibration absorption peak of the ether group, 980.99cm -1 It is a typical absorption peak of a cyclic compound, which indicates that the polymer is a typical polymer of the molecular design of the present invention.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that 90 grams of single-end methyl polyoxyethylene acrylate (MPEGA) is used as single-end vinyl polyether, 30 grams of acrylic acid, and 20 grams of isobornyl methacrylate are used as monomers, potassium persulfate aqueous solution is used as initiator, and sodium hydroxide solution is used as ionizing agent. The other conditions are the same as those in embodiment 1. The obtained product has a similar infrared spectrum to that of embodiment 1.

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that 70 grams of methyl methacrylate (MPEGMA), 60 grams of acrylic acid, and 15 grams of isobornyl methacrylate are used as monomers, and an aqueous sodium persulfate solution is used as an initiator. The other conditions are the same as those in embodiment 1. The obtained product has a similar infrared spectrum to that of embodiment 1.

[0048] Example 4

[0049] The difference between this embodiment and embodiment 1 is that 90 grams of methyl polyoxyethylene methacrylate (MPEGMA), 40 grams of acrylic acid, and 20 grams of isobornyl methacrylate are used as monomers, and an aqueous solution of ammonium persulfate is used as an initiator. The other conditions are the same as those in embodiment 1. The obtained product has a similar infrared spectrum to that of embodiment 1.

[0050] Example 5

[0051] In a reaction four-mouth bottle equipped with a stirrer, a reaction condenser thermometer and a dropping funnel, add 90 grams of allyl polyoxyethylene ether monomer, 60 grams of methacrylic acid, 20 grams of 2-ethylhexyl methacrylate, 1.3 grams of mercaptoethanol (chain transfer agent), and 70 grams of deionized water, and reflux for half an hour. Under reflux conditions, a solution consisting of 60 grams of 0.085M potassium carbonate aqueous solution (ionizing agent) and 1 gram of potassium persulfate (peroxide compound initiator) is added dropwise. After the addition is complete, the reaction is continued for 1 hour, and then the solution consisting of 0.14 grams of potassium persulfate and 14 grams of 0.085M potassium carbonate is added twice, each time at an interval of 1 hour. After the last addition, the reaction is continued at this temperature for 5 hours until the polymerization is complete. Test the infrared spectrum, acid value and solid content.

[0052] Figure 2 This is the infrared spectrum of the product of Example 5. It can be seen from the figure that at the wave number of 2889.66cm-1 There is a very broad absorption peak near 2963 ± 10 cm -1 and 2972±10cm -1 Typical stretching vibration absorption peak of methyl group, 2926±10cm -1 and 2856±10cm -1 A broad absorption peak composed of the typical stretching vibration absorption peaks of methine. 3611.62cm -1 There is a very broad absorption peak, which is a typical carboxyl hydroxyl stretching vibration absorption peak. 1720.07cm -1 This is a typical carbonyl stretching vibration absorption peak in an ester group. 1463.56cm -1 It is the absorption peak of methine deformation vibration, 1112.09cm -1 It is the stretching vibration absorption peak of the ether group. This shows that this type of polymer is a typical polymer of the molecular design of the present invention.

[0053] Example 6

[0054] This embodiment is different from embodiment 5 in that 90 g of allyl polyoxyethylene ether (HPEG), 30 g of acrylic acid, and 10 g of 2-ethylhexyl methacrylate are used as monomers, water-soluble azobisisobutylamidine hydrochloride (AI BA, V-50 initiator) is used as an initiator, and an aqueous sodium carbonate solution is used as an ionizing agent. Other conditions are the same as those in embodiment 5. The obtained product has a similar infrared spectrum to that of embodiment 5.

[0055] Example 7

[0056] This embodiment is different from Example 5 in that 1 gram of allyl polyoxyethylene ether (HPEG), 60 grams of itaconic acid, and 20 grams of octadecyl acrylate are used as monomers, azobisisobutylimidazoline hydrochloride (AI BI, VA-044 initiator) is used as an initiator, and a sodium bicarbonate aqueous solution is used as an ionizing agent. Other conditions are the same as those in Example 5. The obtained product has a similar infrared spectrum to that of Example 5.

[0057] Example 8

[0058] This embodiment is different from the embodiment 5 in that 90 g of allyl polyoxyethylene ether (HPEG), 1 g of methacrylic acid, and 40 g of 2-ethylhexyl methacrylate are used as monomers, azobiscyanovaleric acid (ACVA, V-501) is used as an initiator, and a potassium bicarbonate aqueous solution is used as an ionizing agent. The other conditions are the same as those of the embodiment 5. The obtained product has a similar infrared spectrum to that of the embodiment 5.

[0059] Example 9

[0060] This embodiment is different from the embodiment 5 in that 90 g of allyl polyoxyethylene ether (HPEG), 60 g of acrylic acid, and 1 g of 2-ethylhexyl acrylate are used as monomers, azodiisopropylimidazoline (AIP, VA-061 initiator) is used as an initiator, and tetramethylammonium hydroxide aqueous solution is used as an ionizing agent. The other conditions are the same as those of the embodiment 5. The obtained product has a similar infrared spectrum to that of the embodiment 5.

[0061] Example 10

[0062] This embodiment is different from the embodiment 5 in that 90 g of allyl polyoxyethylene ether (HPEG), 30 g of methacrylic acid, and 20 g of dodecyl methacrylate are used as monomers, and an aqueous solution of ammonium bicarbonate is used as an ionizing agent. The other conditions are the same as those of the embodiment 5. The obtained product has a similar infrared spectrum to that of the embodiment 5.

[0063] Embodiment 11

[0064] In a four-mouth reaction bottle equipped with a stirrer, a reaction condenser thermometer and a dropping funnel, add 90 grams of allyl polyoxyethylene ether monomer, 30 grams of acrylic acid, 20 grams of hexadecyl methacrylate, 1.3 grams of thioglycolic acid, and 70 grams of deionized water, and reflux for half an hour. Under reflux conditions, add a solution consisting of 60 grams of 0.17M sodium hydroxide aqueous solution and 1 gram of ammonium persulfate. After the addition is complete, continue to react for 1 hour, and then add a solution consisting of 0.16 grams of ammonium persulfate and 14 grams of 0.17M sodium hydroxide aqueous solution twice, each time at an interval of 1 hour. After the last addition, continue to react at this temperature for 5 hours until the polymerization is complete. Test the infrared spectrum, acid value and solid content.

[0065] Figure 3 This is the infrared spectrum of the product of Example 11. It can be seen from the figure that the wave number is 2287.12cm -1 There is a very broad absorption peak near 2963 ± 10 cm -1 and 2972±10cm -1 Typical stretching vibration absorption peak of methyl group, 2926±10cm -1 and 2856±10cm -1 A broad peak composed of the typical stretching vibration absorption peak of methine. 3549.25cm -1 It is a typical carboxyl hydroxyl stretching vibration absorption peak. 1728.61cm -1 This is a typical carbonyl stretching vibration absorption peak in an ester group. 1461.61cm -1 It is a typical methine deformation vibration absorption peak. 1110.60cm -1 It is the stretching vibration absorption peak of the ether group, which indicates that this type of polymer is a typical polymer of the molecular design of the present invention.

[0066] Example 12

[0067] In a four-mouth reaction bottle equipped with a stirrer, a reaction condenser, a thermometer and a dropping funnel, add 90 grams of allyl polyoxyethylene ether monomer, 30 grams of acrylic acid, 10 grams of styrene, 1.3 grams of thioglycolic acid, and 70 grams of deionized water, and reflux for half an hour. Under reflux conditions, add a solution consisting of 60 grams of commercially available tetramethylammonium hydroxide aqueous solution and 1 gram of ammonium persulfate. After the addition is complete, continue to react for 1 hour, and then add a solution consisting of 0.16 grams of ammonium persulfate and 14 grams of tetramethylammonium hydroxide aqueous solution twice, each time at an interval of 1 hour. After the last addition, continue to react at this temperature for 5 hours until the polymerization is complete. Test the infrared spectrum, acid value and solid content.

[0068] Figure 4 This is the infrared spectrum of the product of Example 12. It can be seen from the figure that 3017.19 cm -1 It is the phenyl stretching vibration absorption peak, 1564.92cm -1 It belongs to the vibration absorption peak of the phenyl skeleton. At the wave number of 2287.63cm -1 There is a very broad absorption peak near 2963 ± 10 cm -1 and 2972±10cm -1 Typical stretching vibration absorption peak of methyl group, 2926±10cm -1 and 2856±10cm -1 A broad absorption peak composed of the typical stretching vibration absorption peak of methine. 3438.63cm -1 It is a typical carboxyl hydroxyl stretching vibration absorption peak. 1713.97cm -1 This is a typical carbonyl stretching vibration absorption peak in the ester group. 1487.14cm -1 It is the deformation vibration absorption peak of methine. 1109.83cm -1 It is the stretching vibration absorption peak of the ether group, which indicates that this type of polymer is a typical polymer of the molecular design of the present invention.

[0069] The present invention adjusts the type combination and dosage ratio of the reactants on the basis of the above embodiments, and carries out the reaction under the same conditions. The obtained product has an infrared spectrum similar to that of the above embodiments.

[0070] In order to verify the improvement of the conductivity of lithium iron manganese phosphate material by the product of the present invention, the following comparative experiments were conducted by selecting whether to add a conductivity aid to prepare lithium iron manganese phosphate material. All lithium iron manganese phosphate materials in this study were synthesized by combining wet ball milling, spray drying and high temperature solid phase method.

[0071] The specific operations for synthesizing lithium manganese iron phosphate material are as follows.

[0072] (1) Weigh the lithium source, iron source, manganese source, phosphorus source, carbon source, dopant, and additive according to the stoichiometric ratio and mix them. Add deionized water and stir to form a suspension. The solid content is fixed at 50-60%. Place the mixed slurry and zirconia balls in the same ball mill according to the ball-to-material ratio of 5:1. The diameter of the zirconia balls is 0.5 mm. Place the sealed ball mill horizontally in a planetary ball mill and set the ball mill speed to 50 rmin. -1 After ball milling for 2 hours, the precursor slurry was filtered through a 325-mesh screen. A small amount of the precursor slurry was taken with a disposable dropper to measure the slurry viscosity and particle size.

[0073] (2) Connect the spray dryer, and the precursor slurry enters the drying chamber of the spray dryer through the conduit and the peristaltic pump. Under the action of the airflow, the slurry is evenly dispersed into droplets, and spherical powder particles are formed in the drying chamber and brought into the receiving tank by the airflow. The feed inlet temperature of the sprayer is set to 250°C, and the outlet temperature is set to 95°C.

[0074] (3) The obtained precursor powder is placed in a porcelain boat and then placed in a tube furnace for sintering and cooling. The sintering and cooling processes are both carried out under an inert gas atmosphere. After sintering, the product is ground and sieved, and the sieve is selected to have a mesh size of 325 to obtain a finished powder of lithium iron manganese phosphate positive electrode material.

[0075] Comparative Example

[0076] The basic formula of the synthesized iron phosphate material (without conductive additive, adding glucose: polyethylene glycol (PEG) = 75:25, sintering at 650 ° C) was adopted, with d50 of 0.421 μm, d90 of 0.874 μm, viscosity of 6330 mPa.s at 60 rpm, and powder conductivity of 1.949×10 -3 S / cm, compacted density 2.177g / cm 3 .

[0077] Experimental example

[0078] The difference from the comparative example is that the products of Examples 1, 5 and 12 are used to replace polyethylene glycol (PEG), and the other conditions are the same as those of the comparative example. The sintering is carried out at a normal temperature of 650° C. The test results are shown in the following table.

[0079]

[0080]

[0081] By comparing the above experimental examples with the comparative examples, it can be seen that the use of the product prepared by the present invention as a preparation aid for lithium iron manganese phosphate can effectively improve the conductivity, compaction density, etc. of the prepared lithium iron manganese phosphate product. In particular, the conductivity has been greatly improved. The product prepared by the present invention is used in the production of lithium iron manganese phosphate slurry and can also significantly reduce the particle size and viscosity of the prepared lithium iron manganese phosphate slurry, thereby reducing the energy consumption of producing lithium iron manganese phosphate materials and improving product quality.

[0082] Although the above describes the specific implementation methods of the present invention, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.

Claims

1. A special additive for improving the conductivity of lithium manganese iron phosphate powder material, characterized in that: It is prepared by random free radical aqueous solution ionization copolymerization of a single-end vinyl polyether monomer, a vinyl monomer containing an acidic group and other types of vinyl monomers under the action of an initiator and a chain transfer agent; The other types of vinyl monomers are selected from any one or a combination of two or more of styrene, benzyl methacrylate, benzyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylate, dodecyl methacrylate, dodecyl acrylate, hexadecyl methacrylate, hexadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, isobornyl methacrylate, isobornyl acrylate, vinyl pyridine, N-vinyl pyrrolidone, and 4-vinyl phenol.

2. The special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 1, characterized in that: The structural formula is as follows: Where: R1 is -H, -CH3 R2 is -O-(CH2-CH-O) n -H, -COO-(CH2-CH-O) n -CH3; R3 is -H, -CH3; R4 is alkyl, phenyl, pyridyl, pyrrolidone, phenol, benzoic acid; M represents potassium ion, sodium ion, tetramethylammonium cation and hydrogen cation; a, b, c are positive integers.

3. The special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 1, characterized in that: The single-end vinyl polyether monomer is selected from one or a combination of two or more of allyl polyoxyethylene ether (HPEG), single-end methyl polyoxyethylene acrylate (MPEGA), and single-end methyl polyoxyethylene methacrylate (MPEGMA).

4. The special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 1, characterized in that: The vinyl monomer containing an acidic group is selected from any one of acrylic acid, methacrylic acid, itaconic acid and 4-vinylbenzoic acid or a combination of two or more thereof.

5. The special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 1, characterized in that: The mass ratio of the single-end vinyl polyether monomer, the vinyl monomer containing an acidic group, and other types of vinyl monomers is 1-90:1-60:1-60.

6. A method for preparing a special additive for improving the conductivity of lithium iron manganese phosphate powder material according to any one of claims 1 to 5, characterized in that: Single-end vinyl polyether monomer, vinyl monomer containing acidic group and other types of vinyl monomer, chain transfer agent and solvent are added into the reaction container and refluxed at high temperature to react for the first period of time; initiator and ionizing agent solution are added under reflux condition to reflux and react for the second period of time.

7. The method for preparing a special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 6, characterized in that: The single-end vinyl polyether monomers are allyl polyoxyethylene ether, single-end methyl polyoxyethylene acrylate, and single-end methyl polyoxyethylene methacrylate with different molecular weights. The vinyl monomer containing an acidic group is selected from any one of acrylic acid, methacrylic acid, itaconic acid and 4-vinylbenzoic acid. The other types of vinyl monomers are selected from any one of styrene, benzyl methacrylate, benzyl acrylate, 2-ethylhexyl methacrylate, 2-ethylhexyl acrylate, dodecyl methacrylate, dodecyl acrylate, hexadecyl methacrylate, hexadecyl acrylate, octadecyl methacrylate, octadecyl acrylate, isobornyl methacrylate, isobornyl acrylate, vinyl pyridine, N-vinyl pyrrolidone, and 4-vinyl phenol.

8. The method for preparing a special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 6, characterized in that: The solvent is deionized water.

9. The method for preparing a special additive for improving the conductivity of lithium iron manganese phosphate powder material according to claim 6, characterized in that: The initiator is a water-soluble azo initiator or a water-soluble peroxide compound initiator; the water-soluble azo initiator is selected from any one of water-soluble azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobiscyanovaleric acid, and azobisisopropylimidazoline; the peroxide compound initiator is selected from any one of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.

10. Use of the special additive for improving the conductivity of lithium iron manganese phosphate powder material as claimed in any one of claims 1 to 5 in the preparation of lithium iron manganese phosphate powder material.